2008
DOI: 10.1108/09600030810875391
|View full text |Cite
|
Sign up to set email alerts
|

Information sharing, buyer‐supplier relationships, and firm performance

Abstract: Purpose -The purpose of this paper is to examine the effects of information sharing capability on buyer-supplier relationships and firm performance. It is proposed that information sharing capability, the integration of a firm's information/decision systems and business processes with those of supply chain partners, is an antecedent of collaborative buyer-supplier relationships, defined in terms of supply chain and relationship architecture. Further, it is proposed that these relationships positively impact a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
146
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(157 citation statements)
references
References 52 publications
(36 reference statements)
3
146
0
8
Order By: Relevance
“…From the past empirical studies, the frequently measurement for firm size are in terms of employment or total number of employees in the company (Munro & Noori, 1988;Hsu et al, 2008). The size of a firm can also be reflected in its total assets (Yazid et al, 2012) or market capitalization (Ge & McVay, 2005).…”
Section: Firm Sizementioning
confidence: 99%
“…From the past empirical studies, the frequently measurement for firm size are in terms of employment or total number of employees in the company (Munro & Noori, 1988;Hsu et al, 2008). The size of a firm can also be reflected in its total assets (Yazid et al, 2012) or market capitalization (Ge & McVay, 2005).…”
Section: Firm Sizementioning
confidence: 99%
“…They also found that higher inter-firm alignment often results in more, and stronger, lines of communication. Hsu et al (2008) supported this finding by analyzing data from companies in the US, Europe, and New Zealand. They found that successful buyer-supplier relationships had more complex and multi-dimensional communication mechanisms.…”
Section: Literature Reviewmentioning
confidence: 80%
“…invoicing) in a rapid, accurate and transparent manner (Cook et al, 2011). The effectiveness of today's modern supply chain management can be largely attributed to IT tools such as Enterprise Resource Planning (ERP), Electronic Data Interchange (EDI), and the Internet (Akkermans et al, 2003;Hsu et al, 2008). The required information can flow between partner companies rapidly and accurately with these IT tools; thus they create a competitive advantage when compared to other supply chain networks with relatively fewer IT tools (Holweg and Pil, 2008;Paulraj et al, 2008;Gotzamani and Theodorakioglou, 2010).…”
Section: Information Technologymentioning
confidence: 99%
“…The required information can flow between partner companies rapidly and accurately with these IT tools; thus they create a competitive advantage when compared to other supply chain networks with relatively fewer IT tools (Holweg and Pil, 2008;Paulraj et al, 2008;Gotzamani and Theodorakioglou, 2010). Important information such as product availability, inventory level and control, shipment status, new product requirements, demand forecasts and order management can be provided with appropriate IT infrastructures in real-time (Stank et al, 1999;Hsu et al, 2008;Cook et al, 2011). Thus utilizing appropriate IT tools in the supply chain network enables accurate and near real time information flow which helps to achieve competitive performance objectives such as quality, flexibility, responsiveness and dependability and reduced uncertainty (Gunasekaran and Ngai, 2004).…”
mentioning
confidence: 99%